The Effectiveness of Pregnancy Exercises on Sleep Quality in Third Trimester Pregnant Women at the Pratama Arabih Clinic Pekanbaru - Intan Widya Sari; Rina Yulviana (Institute Of Computer Science (IOCS), 2021)
Pregnancy is a critical period in the life of a woman. A period in which changes occur in all body systems, including cardiovascular, respiratory, hormonal, gastrointestinal, and musculoskeletal systems. Pregnant women during pregnancy experience physical and psychological changes that can cause discomfort starting from the first to third trimesters, one of which is sleep disturbances. Sleep disturbances in third trimester pregnant women are caused bydiscomfort, growing stomach, back pain, frequent urination, fetal movement, fatigue, leg cramps, difficulty initiating sleep, and physiological changes. Sleep disturbances result in decreased sleep quality. Pregnancy exercise is an alternative that can break the cycle of anxiety and increase the comfort of pregnant women while sleeping or to reduce the complaints of pregnant women which result in a decrease in the duration of sleep for pregnant women. The purpose of this study was to determine the effectiveness of pregnancy exercise on sleep quality in third trimester pregnant women. The type of research carried out is a quasi-experimental which was carried out on 03-24 September 2020 which was carried out at the Arrabih Pratama Clinic, Pekanbaru City. The population and samples used were all pregnant women who visited in September 2020. The results obtained p value = 0.000, so it was concluded that there was an effect of pregnancy exercise on the sleep quality of third trimester pregnant women (p <0.000). It is hoped that the next research will be able to carry out different interventions to overcome discomfort in pregnant women.